(untitled) (Sustainability in Debate, 2017)
There has been a growing interest in the decentralization of environmental licensing in Brazil. However, few peer-review scholarly studies have evaluated this phenomenon, particularly in the northeastern region. The objective of this paper was to undertake a comparative analysis of the decentralization of environmental licensing in two municipalities in the State of Piauí (Teresina and Água Branca) and two municipalities in the state of Minas Gerais (Belo Horizonte and Betim). The study adopted a qualitative methodological approach based on multiple case studies analysis. Data were collected from content analysis and structured interviews. The study found significant institutional and regulatory differences among the state and municipalities. The quality of the municipal environmental licensing system is seemingly related to administration size and local socioeconomic conditions, but further studies are needed to confirm this finding. The interviewees’ perceptions corroborate previous studies that identified lack of human resources and infrastructure as key barriers to environmental licensing at the municipal level. The study concludes with suggestions for future research avenues.